Improve Performance Of Watchkeeping Duties By Fix Overtimes Analysis In MT. Ontari PT. Buana Listya Tama - Afdolludin Afta Tazani; Tony Santiko (IWJ : Inland Waterways Journal, 2020)
Fix overtime on MT. Ontari at PT. Buana Listya Tama, can help Crews finish work on time with limited time, but the implementation of fix overtime at PT. Buana Listya Tama has not been going well to improve the performance. The purpose of this study is to determine the cause of fix overtime in order to improve the performance of Watchkeeping are given to Ship Crews to improve. This research uses descriptive qualitative method which will reveal facts, phenomena, variables and conditions that occur when the research is going on regarding fix overtime experienced by Crews. The results of the study indicate the causes of fix overtime including, the role of the rear face when leaning or off the dock, existence of anchor, loading and unloading, drill, bunkering, and ship engine maintenance. Policy of the fix overtime are not comfortable so many crew want to sign off before the contract expires, and the policy of fix overtime there are problems or obstacles that need time and process for the creation of efforts or steps taken can realized business that can be done including, increasing salaries, providing incentives and compensation and vessel allowance to the crew at PT. Buana Listya Tama.